2017
DOI: 10.1111/jam.13364
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic roles ofLactobacillussp. in swine: insights from gut microbiota

Abstract: SummaryThe use of lactobacilli as probiotics in swine has been gaining attention due to their ability to improve growth performance and carcass quality, prevent gastrointestinal infection and most importantly, their 'generally recognized as safe' status. Previous studies support the potential of lactobacilli to regulate host immune systems, enhance gut metabolic capacities and maintain balance in the gut microbiota. Research on swine gut microbiota has revealed complex gut microbial community structure and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(181 citation statements)
references
References 98 publications
(182 reference statements)
4
146
0
6
Order By: Relevance
“…Previous studies have reported that oral administration of Lactobacillus changes the structure of the gut microbiota, influencing intestinal mucosal immunity and host metabolism (Valeriano et al, ). For example, administration of L. frumenti JCM 11122 increased the abundance of L. frumenti in the faeces of early weaned piglets, and treatment with L. reuteri ZLR003 significantly altered the microbial diversity and community composition in the intestinal contents of weaned piglets (Hu et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that oral administration of Lactobacillus changes the structure of the gut microbiota, influencing intestinal mucosal immunity and host metabolism (Valeriano et al, ). For example, administration of L. frumenti JCM 11122 increased the abundance of L. frumenti in the faeces of early weaned piglets, and treatment with L. reuteri ZLR003 significantly altered the microbial diversity and community composition in the intestinal contents of weaned piglets (Hu et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus colonizes the proximal and distal regions of the porcine digestive tract soon after birth and is one of the core genera in the gastrointestinal tracts of pigs (Mesquita et al, ; Valeriano, Balolong, & Kang, ). Many studies have revealed that Lactobacillus has the potential to regulate host immune systems, enhance gut metabolic capacities and maintain balance in the gut microbiota (Hou, Zeng, Yang, Liu, & Qiao, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the human study [45], this was a longterm effect in our study, probably as a consequence of an impaired maturation of the microbiota, as this effect was only detectable on day 97 of life. Members of the Lactobacillaceae are known to have many health promoting properties [46] including prevention of adhesion of opportunistic pathogens via attaching to the mucus layer in the gut [47]. They also produce lactate which is utilized by other bacteria to convert it into propionate, valerate, and butyrate [48].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lactic acid bacteria (LAB) are regarded as safe by the FDA [70]. Many of these bacteria are symbiotic with their hosts.…”
Section: Application Strategies Of Antimicrobial Peptidesmentioning
confidence: 99%